The Role of Transformational Leadership in Enhancing Employee Creative Performance (International Journal of Financial, Administrative and Economic Sciences, 2026)
This study aimed to examine the role of transformational leadership in enhancing employees' creative performance through a review and analysis of the relevant literature and previous studies that investigated the relationship between transformational leadership, with its various dimensions, and creative performance in organizations. The significance of this study stems from the growing need to adopt modern leadership approaches capable of fostering employees' creativity and innovation in light of the rapid changes taking place in contemporary work environments, thereby contributing to improved organizational performance and the achievement of sustainable competitive advantage.The study adopted a descriptive-inductive approach by reviewing and analyzing relevant Arabic and international literature and previous studies related to the research topic. The findings revealed that transformational leadership is one of the most influential leadership styles in enhancing employees' creative performance due to its ability to inspire employees, motivate them, develop their capabilities, encourage innovative thinking, and promote their participation in work improvement initiatives. The literature analysis also indicated that the dimensions of transformational leadership—idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration—play an integrated role in creating an organizational environment that supports creativity by fostering trust, empowering employees, encouraging initiative, facilitating knowledge sharing, and promoting continuous learning.Furthermore, the study found that most previous studies agreed on the positive impact of transformational leadership on improving various dimensions of organizational performance, including job performance, human resource performance, organizational success, innovative work behavior, and innovation culture. These findings provide theoretical support for the relationship between transformational leadership and employees' creative performance. The study also identified a need for further research, particularly in the Arab context, to investigate the direct relationship between transformational leadership and employees' creative performance, thereby helping to address the existing research gap in this field.
Keywords: Transformational Leadership; Creative Performance; Organizational Creativity; Employees; Inspirational Motivation